VIREO@TRECVID 2011: Instance search, semantic indexing, multimedia event detection and known-item search - NGO, Chong-wah (Institutional Knowledge at Singapore Management University, 2011)
The vireo group participated in four tasks: instance search, semantic indexing, multimedia event detection and known-item search. In this paper,we will present our approaches and discuss the evaluation results.